Maintaining pH-dependent conformational flexibility of M1 is critical for efficient influenza A virus replication - Meng-Jung Chiang; Faik N Musayev; Martina Kosikova; Zhengshi Lin; Yamei Gao; Philip D Mosier; Bashayer Althufairi; Zhiping Ye; Qibing Zhou; Umesh R Desai; Hang Xie; Martin K Safo (Emerging Microbes and Infections, 2017)
The M gene segment of influenza A virus has been shown to be a contributing factor to the high growth phenotype. However, it remains largely unknown why matrix protein 1 (M1), the major structural protein encoded by M gene, exhibits pH-dependent conformational changes during virus replication. Understanding the mechanisms underlying efficient virus replication can help to develop strategies not only to combat influenza infections but also to improve vaccine supplies. M(NLS-88R) and M(NLS-88E) are two M1 mutants differing by only a single amino acid: G88R vs G88E. G88R but not G88E was the compensatory mutation naturally selected by the virus after its nuclear localization signal was disrupted. Our study shows that, compared with M(NLS-88E) M1, M(NLS-88R) M1 dissociated quickly from viral ribonucleoproteins (vRNPs) at higher pH and took less time to dissemble in vitro, despite forming thicker matrix layer and having stronger association with vRNP in assembled virions. Correspondingly, M(NLS-88R) replicated more efficiently and was genetically more stable than M(NLS-88E). Crystallographic analysis indicated that M(NLS-88R) M1, like wild-type M1, is able to switch from a face-to-back-oriented conformation to a face-to-face-oriented conformation when pH drops from neutral to acidic, whereas G88E mutation causes M(NLS-88E) M1 to be trapped in a face-to-face-arranged conformation regardless of environmental pH. Our results suggest that maintaining M1 pH-dependent conformational flexibility is critical for efficient virus replication, and position 88 is a key residue controlling M1 pH-dependent conformational changes. Our findings provide insights into developing M1-based antiviral agents.Emerging Microbes & Infections (2017) 6, e108; doi:10.1038/emi.2017.96; published online 6 December 2017